2006
DOI: 10.1016/j.cviu.2006.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A unifying geometric representation for central projection systems

Abstract: In this paper, we study projection systems with a single effective viewpoint, including combinations of mirrors and lenses (catadioptric) as well as just lenses with or without radial distortion (dioptric systems). First, we extend a well-known unifying model for central catadioptric systems to incorporate a class of dioptric systems with radial distortion. Second, we provide a new representation for the image plane of central systems. This representation is the lifting through a Veronese map of the original i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 18 publications
0
52
0
2
Order By: Relevance
“…Section 3.1.7) and the division model. A similar extension was proposed by Barreto, who showed that when replacing the sphere with a paraboloid, one may represent the division model [26,27].…”
Section: Global Camera Models 55mentioning
confidence: 95%
See 1 more Smart Citation
“…Section 3.1.7) and the division model. A similar extension was proposed by Barreto, who showed that when replacing the sphere with a paraboloid, one may represent the division model [26,27].…”
Section: Global Camera Models 55mentioning
confidence: 95%
“…The second method is of the bundle adjustment type; it estimates the distortion model's coefficients using as cost function the Sampson distance between image points and line images (conics). Barreto as well as Strand and Hayman proposed similar plumb-line methods for the 1-parameter division model, for which line images are circles [26,466].…”
Section: Lines -The Plumb-line Approachmentioning
confidence: 99%
“…The unitary sphere represents an other space which is particularly useful for omnidirectional image processing. As demonstrated in [5] and [6], there exists an equivalence between the unitary sphere and single view point (SVP), also called central images and even some fisheye images [7]. However, this equivalence is related to the knowledge of the intrinsic parameters of the sensor ( fig 3) and can be decomposed into a double projection as follows: 3D point P w is projected on the sphere surface according to the sphere center in P s which is then projected on the image plane into P i from the projection center O p located between the center and the north pole of the sphere.…”
Section: Introductionmentioning
confidence: 91%
“…The polynomial approximation of the projection function was introduced by Scaramuzza (Scaramuzza et al, 2006), who proposed a calibration toolbox for his model. The generic model, also known as the unified model, was introduced by Geyer (Geyer & Daniilidis, 2000) and Barreto (Barreto, 2006), who proved its validity for all central catadioptric systems. This model was then modified by Mei (Mei & Rives, 2007), who generalized the projection matrix and also took into account the distortions.…”
Section: Projection Modelmentioning
confidence: 99%